2021
DOI: 10.1177/23779608211035208
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge in Relation to the Anorexia–Cachexia Syndrome in Cancer Patients: A Cross-National Comparison in Two European Countries

Abstract: Introduction The Anorexia–Cachexia Syndrome (ACS) is a severe complication of cancer and is considered to be a significant cause of morbidity and mortality affecting up to two-thirds of cancer patients and one that needs specialized nursing care. Studies showed that the ACS has been relatively under-researched and under-resourced whist the nurses’ knowledge has not been systematically explored. Objective Τo explores nurses’ knowledge, understanding, and management of ACS in clinical practice in two European co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Despite the importance of introducing these interventions clinically, there is a lack of clinical guidelines as well as data to inform such practice, particularly in the acute care setting [ 43 ]. Similarly, decreased appetite has also been reported as a debilitating chemotherapy-triggered symptom but is often underappreciated and undermanaged in cancer care [ 44 ]. Although poor appetite inducing malnutrition has been widely recognized, current cancer supportive care regimens specifically targeting chemotherapy-related appetite loss are sparse and unavailable to many remote and regional settings [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of introducing these interventions clinically, there is a lack of clinical guidelines as well as data to inform such practice, particularly in the acute care setting [ 43 ]. Similarly, decreased appetite has also been reported as a debilitating chemotherapy-triggered symptom but is often underappreciated and undermanaged in cancer care [ 44 ]. Although poor appetite inducing malnutrition has been widely recognized, current cancer supportive care regimens specifically targeting chemotherapy-related appetite loss are sparse and unavailable to many remote and regional settings [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“… 49 It is reported that knowledge and education related to cancer cachexia is lacking among medical professionals; that multidisciplinary cooperation cannot be practiced; that the roles and responsibilities of each team member are not clearly defined. 50 , 51 , 52 , 53 Clinical trials of multidisciplinary interventions which combine drug therapy, nutritional therapy, and exercise therapy are currently underway, and it is hoped that the results will lead to the broad development and implementation of multidisciplinary patient support systems across medical institutions.…”
Section: Future Challenges In the Treatment Of Cancer Cachexia By Mul...mentioning
confidence: 99%
“… Japan Socratous et al. 13 2021 n ​= ​197, cancer nurses 75% report no formal education in cachexia. Greece and Cyprus Murphy et al.…”
Section: Introductionmentioning
confidence: 98%
“…Nurses may be educating patients and their family members in cancer cachexia and its management, with their contribution unstudied and, therefore, not reported. Yet surveys of cancer and palliative care clinician knowledge and practice of guideline recommended cachexia care have found a lack of formal education and know-how 8 , 9 , 10 , 11 , 12 , 13 , 14 ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%